Al-Nasawiyyah fi Riwāyah Zīnah li Nawal al-Sa’adāwi - Merdu Arika (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
Literature have widely described the women existence and inequality. Feminist literary criticism is a study which focuses on analysis of women demanding justice of their existence. It also describes the elements of inequality occurred in